2009
DOI: 10.2478/s11658-009-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a new approach to the regeneration of Helichrysum italicum (Roth) G. Don, and the molecular characterization of the variation among sets of differently derived regenerants

Abstract: A protocol for the induction of regeneration from leaves of Helichrysum italicum was established. Calli were found to form on the basal medium only when it was supplemented with thidiazuron (TDZ) alone or in combination with naphthalene acetic acid (NAA), with a percentage ranking of at least 80%. The hormone-free medium showed the highest percentage of shoot regeneration (62%) even though no callus formed. AFLP markers were employed to verify tissue culture-induced variation in the regenerated plantlets obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…This result was similar with the findings of (Tawfik (1992) who cleared that TDZ could alone induce nodular meristematic callus, and Perrini et al (2009) who found that Callus of Helichrysum italicum were found to form on the basal medium only when it was supplemented with thidiazuron (TDZ) alone or in combination with naphthalene acetic acid (NAA). .…”
Section: Figure (3): Effect Of the Transplanting Media On Increase Insupporting
confidence: 90%
“…This result was similar with the findings of (Tawfik (1992) who cleared that TDZ could alone induce nodular meristematic callus, and Perrini et al (2009) who found that Callus of Helichrysum italicum were found to form on the basal medium only when it was supplemented with thidiazuron (TDZ) alone or in combination with naphthalene acetic acid (NAA). .…”
Section: Figure (3): Effect Of the Transplanting Media On Increase Insupporting
confidence: 90%
“…The extent of DNA marker polymorphism can, however, vary considerably between plant materials - even of the same species - as was shown by comparing the very uniform regenerants of the banana cultivar 'Prata Ana’ [ 139 ] with the highly variable regenerants of cultivar 'Valery’ [ 140 ]. When AFLP analysis was applied to regenerants of Helichrysum italicum , plantlets derived directly from leaves showed the same level of variability as plantlets that had passed through a callus stage [ 141 ]. Although only 6.2% of a total of 449 bands were polymorphic, almost all plantlets differed from the original genotype in at least one band.…”
Section: Present-day Fingerprinting Of Plantsmentioning
confidence: 99%
“…The plants belonging to the genus Helichrysum (family Asteraceae) are known as everlasting flowers and are widely used in traditional medicine worldwide [ 4 ]. The plant species of this genus typically have inflorescences of a bright yellow color [ 5 ], which retain their form and color when dried, hence the name “everlasting” or “immortal” [ 4 ]. The stems are woody at the base and can reach 30–70 cm in height.…”
Section: Introductionmentioning
confidence: 99%